Intrahepatic Pseudoaneurysm Developing at the Confluence of Bilateral Biliary Drains Six Months Following a Procedure- A Case Report - Qtaish, Izzeddin; Ayasrah, Mohammad; Qtaish, Noat R. (Current Medical Imaging, 2024)
Background:Hepatic artery aneurysms (HAAs) exhibit a notable risk of rupture, with both true aneurysms and pseudoaneurysms being exceptionally uncommon (incidence rate approximately 2 per 100,000). Symptoms include epigastric and right upper quadrant pain, jaundice, and potentially life-threatening bleeding upon rupture. This bleeding can extend into the portal vein, hepatic vein, biliary system, or abdominal cavity. While existing literature lacks reports of delayed post-therapeutic complications, this case report discusses a 27-year-old female who developed a pseudoaneurysm six months after bilateral biliary drain insertion, underscoring the potential for delayed complications.Case Presentation:The patient underwent gastric endoscopy revealing an extensive lower esophageal varix protruding into the proximal stomach, subsequently treated with banding. The stomach and duodenum were found to contain fresh blood and blood clots indicating acute bleeding.An urgent CT scan identified active bleeding (extravasation) at segment V and blood accumulation at the confluence of the right and left biliary drains. This was followed by celiac and selective hepatic digital subtraction angiography (DSA).Conclusion:This case study outlines the occurrence of a hepatic artery pseudoaneurysm six months after percutaneous insertion of bilateral biliary drains. The pseudoaneurysm manifested precisely at the confluence of the right and left drains. The reported delayed complication may have resulted from friction between the drains at the confluence or erosion of the adjacent artery by the drains. The insights gained from this case shed light on the causes and preventive measures for potential delayed complications associated with percutaneous biliary drain placement.
Keywords: liver injury